PENGARUH KONSENTRASI PUPUK LIMBAH CAIR CUCIAN BERAS DAN DOSIS PUPUK KASCING TERHADAP PERTUMBUHAN DAN HASIL TANAMAN MENTIMUN (Cucumis sativus L.) - Fatur, Tiyo; Priyono, Priyono; Bahri, Saiful (Institute of Computer Science (IOCS), 2025)
Effect of concentration of liquid waste from rice washing and dose of vermicompost fertilizer on growth and yield of cucumber (Cucumis sativus L.). Cucumber is one of the annual plants that are creeping or creeping which is included in the pumpkin family (Cucurbitaceae). This research have been conducted on January 8th 2025 until February 25th 2025 in Gabugan village, Tanon Subdistrik, Sragen regency, at Grumosol soil type with the place hight 110 meters above the sea level. The purpose of the study was to determine the effect of concentration of liquid waste from rice washing and dose of vermicompost fertilizer on growth and yield of cucumber (Cucumis sativus L.) plants. The experimental design used was a completely randomized block design (CRBD), consisted of two treatment and three replications. The first factor were concentration of liquid waste from rice washing (K), consisted of three level (K0 = 0 ml/l, K1 = 36 ml/l and K2 = 72 ml/l). The second factor were dose of vermicompost fertilizer (D) consisted of three level (D0 = 0 ton/ha, D1 = 15 ton/ha and D2 = 30 ton/ha). The provision of liquid waste fertilizer from rice washing, there was a significant effect on plant length, fresh weight of stover, dry weight of stover, number of fruit per plant, weight of fruit per plant and weight of fruit per plot. The application of liquid rice washing waste fertilizer at a concentration of 36 ml/l to 72 ml/l resulted in an increase in the growth and yield of cucumber plants. The provision of vermicompost fertilizer has a significant effect on plant length, fresh weight of stover, dry weight of stover, number of fruit per plant, weight of fruit per plant and weight of fruit per plot. The application of vermicompost fertilizer at a dose of 15 tons/ha up to a dose of 30 tons/ha, the growth and yield of cucumber plants still increased. The combination of liquid waste concentration from washing rice and the dose of vermicompost fertilizer did not have a significant interaction with plant length, fresh weight of stover, dry weight of stover, number of fruit per plant, weight of fruit per plant and weight of fruit per plot. Application of liquid rice washing waste fertilizer at a concentration of 72 ml/l and vermicompost at a dose of 30 tons/ha, the weight of fruit per plot is 28,20 kg/ha, cucumber plants still experience a positive response.